2018
DOI: 10.1080/0158037x.2018.1447918
|View full text |Cite
|
Sign up to set email alerts
|

Liminal practice and reflection in professional education: police education and medical education

Abstract: This paper reports on a study of how liminality relates to the facilitation of reflective practice in professional education. Liminality refers to sites and positions that exhibit 'in-betweenness', or bordering positions, that might draw together different institutional conditions. The present project aims to examine the role of liminality in professional educational practice with a specific focus upon how liminality may support student reflection. Using a qualitative and comparative research approach, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
0
15
1
1
Order By: Relevance
“…There was some evidence of the reassertion of masculinity among this group in that they were the most likely to witness sexualised joking and banter and 7 of 10 complained of gendered stereotypical tasking. This differed from findings by Rantatalo and Lindberg (2018) when examining Swedish police officer students. They found a state which could be characterised as transitory (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There was some evidence of the reassertion of masculinity among this group in that they were the most likely to witness sexualised joking and banter and 7 of 10 complained of gendered stereotypical tasking. This differed from findings by Rantatalo and Lindberg (2018) when examining Swedish police officer students. They found a state which could be characterised as transitory (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, our respondents were established police officers who were reflecting on change by comparing their present experiences with those of the past. We were not looking at the new intake of student officers who might be in the transitory liminal state reported by Rantatalo and Lindberg (2018). Nonetheless, the authors believe the results generate plausible hypotheses to be confirmed by further analysis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Posisi liminal yang dialami oleh performativitas dalam praktik pembelajaran musik berbasis teknologi digital terkait dengan bergesernya aspek pedagogis (Kladder, 2020;Rantatalo & Lindberg, 2018). Perkembangan teknologi digital yang cepat tidak diimbangi oleh kecepatan perkembangan aspek pedagogis.…”
Section: Pendahuluanunclassified
“…According to Turner (1969), individuals experience liminality when they are situated within a blend of structures, i.e., hierarchical and differentiation along with non-structural attributes, i.e., a break with the roles, routines and constraints of normative reality. Thus, liminality draws together different institutional conditions that contain overlaps of formal and informal dimensions, or a creative combination of institutional and anti-institutional elements (Lindsay, 2010;Rantatalo and Lindberg, 2018). Recently, liminality is regarded as a permanent position and as an "ongoing state of affairs" of everyday life … that is "neither this nor that" (Söderlund and Borg, 2018, p. 887), which provides an understanding of the human experiences under the conditions of the modern society and late modernity (Beck, 2000;Turner, 1977).…”
Section: The Liminal Frameworkmentioning
confidence: 99%